Problemy sovershenstvovaniya sportivnogo masterstva v volnoj borbe - Podlivaev, B. A.; Nevretdinov, S. E.; Susnin, Yu. M. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
On the problems of perfection of sports skill in freestyle wrestling and the sport results in freestyle wrestling in the last years (Russian and international, specially Olympic Games 2000 and WM 2001 and 2002).